2023
DOI: 10.3390/met13010144
|View full text |Cite
|
Sign up to set email alerts
|

The Corrosion Behavior of WEDM Machined Stainless Steels in a Pyrolysis Environment

Abstract: Pyrolysis represents one of the most convenient technologies for the chemical transformation of waste. The exposure to corrosion products and high temperatures does, however, require chemically resistant construction materials. This study was carried out to analyze the corrosion behavior of 1.4571 (AISI 316Ti) and 1.4305 (AISI 303) stainless steels machined with wire electric discharge machining (WEDM) in a pyrolysis environment. Different machining parameters were used for both materials tested to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This material is commonly used in the petrochemical and chemical industries, where corrosion resistance at high temperatures is required [160]. In fact, due to its superior strength, resistance to high temperatures, and anticorrosive qualities, particularly in harsh environments, it is widely used in nuclear reactors [161][162][163][164][165], boilers [166][167][168], pipelines [169,170], heat exchangers [171][172][173], furnaces [174,175], and the oil and gas and chemical industries [176]. Due to the high mechanical strength and corrosion resistance, AISI 316L stainless steel is also used as a filter in food processing industries, where the stainless steel filters are subjected to severe conditions associated with the removal of solid particles from fluids [177][178][179].…”
Section: Applicationsmentioning
confidence: 99%
“…This material is commonly used in the petrochemical and chemical industries, where corrosion resistance at high temperatures is required [160]. In fact, due to its superior strength, resistance to high temperatures, and anticorrosive qualities, particularly in harsh environments, it is widely used in nuclear reactors [161][162][163][164][165], boilers [166][167][168], pipelines [169,170], heat exchangers [171][172][173], furnaces [174,175], and the oil and gas and chemical industries [176]. Due to the high mechanical strength and corrosion resistance, AISI 316L stainless steel is also used as a filter in food processing industries, where the stainless steel filters are subjected to severe conditions associated with the removal of solid particles from fluids [177][178][179].…”
Section: Applicationsmentioning
confidence: 99%
“…In addition, they also concluded that under these conditions, relatively fewer craters, pockmarks, cracks, and pulled-out material were found on the wire electrodes and work specimen surfaces. Benes et al [36] experimentally showed that a surface machined using WEDM experiences surface hardness, a change in the elemental characteristics of the subsurface of the recast layer, and a tendency to become a heat-affected zone. Because of the surface's impurities and fractures, surfaces that undergo WEDM are likely to have a high level of corrosive adoptability.…”
Section: Introductionmentioning
confidence: 99%